STUDY OF BELITE STRUCTURE CHANGES INFLUENCED BY POTASSIUM - Fridrichová M.; Dvořák K.; Gazdič D. (Ceramics-Silikáty, 2013)
The production of clinker is carried out by burning process of raw material mixture modified by potassium ions in the form of potash (K2CO3). The potash carbonate is dosed in amounts ranging from 0 % to 3 mass %. Potassium ions are involved in clinker creation process and causing microstructure defects. These defects lead to increase of reactivity and thus increase of velocity of hydration process. Due to temperature instability of potassium ions at usual temperature of clinker burning process around 1250°C, temperature regimes of 950 and 1100°C were tested with isothermal times of 1, 3, 5 hours. Phase composition, physico-mechanical properties and hydration process were observed.